An inquiry into the political economy of the global clean energy transition policies and Nigeria's federal and state governments' fiscal policies - David Onyinyechi Agu; Evelyn Nwamaka Ogbeide-Osaretin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In order to implement clean energy transition programmes, the national and sub-national governments in Nigeria will incur some cost. In the same way, failure to implement the policies will come with some costs. This paper therefore considers the fiscal policy implications of Nigerian governments' implementation of clean energy transition policies in the country. The analysis also reveals that the observed reluctance of Nigerian governments in implementing the policies is obviously unconnected with their dependence on oil revenues. The paper further presents the fiscal policy implications of Nigerian governments' inaction even when other countries implement their clean energy transition policies.
Keywords: H50; H72; Q38; Q42; 330; fossil fuel; clean energy; federal government; state governments; fiscal policies; fiscal shocks